Study of trapping phenomenon in 4H-SiC MESFETs dependence on substrate purity. - Sghaier, N. (IEEE Transactions on electron devices)
This work demonstrates that the "purity", meaning the low density of electron traps in a semi-insulating (SI) SiC substrate, can be crucial for the electrical characteristics of 4H-SiC MESFETs. Structures realized on two types of SI substrates have been investigated. The first kind is vanadium doped substrates grown by the classical Physical Vapor Transport (PVT) sublimation technique. The second kind are extremely low vanadium content SI substrates grown by the high temperature CVD (HTCVD) technique. For all the transistors, Id-Vds measurements have been performed as a function of temperature. Different parasitic effects have been observed on the static output characteristics in the case of PVT substrates. Frequency dispersion measurements of the transconductance and drain-source output conductance, have next been realized. The results give clear evidence of the presence of deep traps in the transistors realized on PVT substrates. Those traps have an activation energy of 1.05 eV and a capture cross section between 10-18 cm-2 and 10-19 cm-2. They are most probably related to vanadium. The correlation between the presence of these traps and the parasitic effects on the output characteristics is discussed and the trap localization in the structure is established. In the case of HTCVD very low vanadium substrates, no parasitic effect have been observed and the presence of traps was not detected by the different characterization techniques.